2004
DOI: 10.1097/01.opx.0000145020.33250.c0
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of IOLMaster Biometry in Children

Abstract: Partial coherence interferometry techniques, such as that used by IOLMaster, should be considered as the standard technique for axial length measurement in children because they are noninvasive, highly precise, and easy to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 18 publications
6
88
1
3
Order By: Relevance
“…16,26 In children, the reported repeatability differs widely among researchers (±0.23-0.85 mm), 17,18 presumably because the repeatability is dependent on how much cooperation was obtained from the children. Compared with these values, the repeatability of the IOLMaster measurement that we found in children was 5 to19 times more precise.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…16,26 In children, the reported repeatability differs widely among researchers (±0.23-0.85 mm), 17,18 presumably because the repeatability is dependent on how much cooperation was obtained from the children. Compared with these values, the repeatability of the IOLMaster measurement that we found in children was 5 to19 times more precise.…”
Section: Discussionmentioning
confidence: 93%
“…Another advantage of this device is its high precision. 15,16 In children, Carkeet et al 17 and Hussin et al 18 reported that test-retest repeatability of this measurement was ±0.047 mm and ±0.04 mm, respectively (Table 1). However, these studies provided no information regarding refractive errors in the subjects, and thus it is still unknown whether the reported repeatability can be expected in children with a wide range of refractive errors.…”
mentioning
confidence: 96%
“…The repeatability of ultrasound biometry in children was found acceptable in a previous study. 30 The optometrists performing the above effi cacy measurement and visual acuity testing were masked regarding the treatment that the children received. To detect any adverse effects, careful and comprehensive examination, including slit-lamp and fundus examination, was performed by a single ophthalmologist for all subjects on a trimonthly basis.…”
Section: Methodsmentioning
confidence: 99%
“…Partial coherence interferometry has not been previously studied in preschoolers, but it has been demonstrated to be more reproducible than A-scan ultrasonography in measuring axial length in school age children. 9,10 Ophthalmologists and optometrists with pediatric subspecialty training performed all of the tests in this study. Testability of preschoolers with these devices using non-professionals in a screening setting may thus be less.…”
mentioning
confidence: 99%